Microbial Inoculants Modulate Physiological Behaviour Of Troyer Citrange Under Drought Stress (Bangladesh Journal of Botany, 2021)
A study was undertaken with Troyer citrange (Citrus sinensis × Poncirus trifoliata), the rootstock of citrus, to elucidate the interaction effects of arbuscular mycorrhizal fungi and plant-growth-promoting bacteria on plant physiology under both ample watered and water stress conditions. The result exhibited significant influence of Glomus intraradices and phosphorus solubilising bacteria (PSB) (mixture of Bacillus subtilis and B. megatherium) on plant growth due to root-fungus-bacteria interaction leading to reduced accumulation of reactive oxygen species, production of antioxidant metabolites, higher anti-scavenging enzymes and higher acquisition of plant nutrients, besides enhancing rhizosphere microbial activity. Thus, Troyer citrange could be co-inoculated with G. intraradices and PSB during propagation for healthy growth of the seedlings thereby pre-ponding the budding and subsequent establishment of composite plants under field conditions.Bangladesh J. Bot. 50(3): 467-474, 2021 (September)